THE IMPACT OF LIFE SKILL EDUCATION CURRICULUM IMPLEMENTATION IN ANTICIPATING ADOLESCENT PROBLEMS AT THE UNICEF PROJECT PILOT SCHOOL IN BONE REGENCY - Nursabaha, Sarifa; Juhannis, Hamdan; Syamsudduha, St.; Mania, Sitti (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2022)
This article aims to determine the impact of implementing Life Skill Education curriculum in anticipating adolescent problems at Unicef ​​Pilot Project School in Bone. Data collection techniques include interviews, observations, and documents. The data were analyzed by the stages of data display, data reduction, and data verification. The results showed that the impact of implementing LSE curriculum in anticipating adolescent problems in Bone was seen in independence of meeting personal needs in the form of students being able to be independent, gaining life skills, being able to overcome problems of Menstrual Hygiene Management (MKM), and being able to practice a variety of learning methods. Other independence in terms of meeting social needs are students being able to overcome bullying problems, managing environment, and overcoming child marriage. Therefore, it is expected to the government to issue a policy on the implementation of Life Skill Education curriculum to be applied in the educational environment because it has a positive influence on the prevention of child marriage. Abstrak: Artikel ini bertujuan untuk mengetahui dampak implementasi kurikulum Life Skill Education dalam mengantisipasi problematika remaja pada Sekolah Pilot Project Unicef di Kabupaten Bone. Teknik pengumpulan data diperolah meliputi wawancara, observasi dan dukumen. Data dianalisis dengan pendekatan kualitatif lalu diolah dengan tahap display data, reduksi data, dan verifikasi data. Hasil penelitian menunjukkan bahwa dampak implementasi kurikulum Life Skill Education dalam mengantisipasi problematika remaja di Bone terlihat pada kemandirian pemenuhan kebutuhan personal berupa: peserta didik mampu bersikap mandiri, peserta didik memperoleh keterampilan hidup, peserta didik mampu mengatasi masalah Manajemen Kebersihan Menstruasi (MKM), peserta didik mengetahui dan mampu mempraktikkan metode pembelajaran yang bervariasi. Kemandirian lainnya dalam hal pemenuhan kebutuhan sosial, berupa: peserta didik mampu mengatasi masalah bullying, mengelola lingkungan, dan mengatasi persoalan perkawinan anak. Implikasi penelitian diharapkan kepada pemerintah terkait untuk mengeluarkan kebijakan tentang implementasi kurikulum Life Skills education untuk diterapkan di lingkungan pendidikan karena memiliki pengaruh positif terhadap pencegahan perkawinan anak.